2020
DOI: 10.1101/2020.01.08.897728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On mechanisms of light-induced deformations in photoreceptors

Abstract: Photoreceptors in the retina convert light into electrical signals through a phototransduction cycle that consists of multiple electrical and biochemical events. Phase-resolved optical coherence tomography (pOCT) measurements of the optical path length (OPL) change in the cone photoreceptor outer segments after a light stimulus (optoretinogram) reveal a fast, ms-scale contraction by tens of nm, followed by a slow (hundreds of ms) elongation reaching hundreds of nm. Ultrafast measurements with a line-scan pOCT … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Second, it matches the time course of the deformation at different stimulus intensities, specifically the earlier time to peak at higher stimulus intensity, as shown in Fig 3c (also see Fig 2f and Fig S2). The excellent agreement of the model with the experimental results, being consistent in peak deformation and timing across all stimulus intensities with a single set of model parameters ( , , , and ), indicates that the contraction of the outer segment is an optical signature of the ERP 29 .…”
Section: Energy Dependence Of the Early And Late Cone Responsesupporting
confidence: 63%
See 1 more Smart Citation
“…Second, it matches the time course of the deformation at different stimulus intensities, specifically the earlier time to peak at higher stimulus intensity, as shown in Fig 3c (also see Fig 2f and Fig S2). The excellent agreement of the model with the experimental results, being consistent in peak deformation and timing across all stimulus intensities with a single set of model parameters ( , , , and ), indicates that the contraction of the outer segment is an optical signature of the ERP 29 .…”
Section: Energy Dependence Of the Early And Late Cone Responsesupporting
confidence: 63%
“…Here we outline the key components of the model. A more detailed elaboration of the model appears in a companion article 29 . The membrane area expansion coefficient increases with tension as a result of flattening the thermally induced fluctuations 30 .…”
Section: Energy Dependence Of the Early And Late Cone Responsementioning
confidence: 99%
“…The late response has been attributed to be the influx of water to maintain osmotic balance during the phototransduction cascade 15 . Based on the latency and the magnitude of the stimulus strength that characterize the rapid shrinkage, we earlier concluded that the reduction in OPL is the optical manifestation of the early receptor potential observed previously in vitro, attributed to charge movement across the outer segment disc membranes during photoisomerization 39,[45][46][47] . Similar experiments as Figure 5 were repeated with the increased resolution offered by AO that allowed discerning the ORG in individual cones, in response to the 660 nm stimulus.…”
Section: Figure 5: Optoretinograms With 660 Nm Stimulus Acquired Withmentioning
confidence: 89%
“…The key featureshigh speed, anamorphic detection, AO or non-AO operationsummarized above are fundamental to the application of this novel technology for interferometric imaging of neural activity in photoreceptors and holds promise for future applications to other retinal cells in general. While this work represents an important step forward in the technology for all-optical, non-invasive interrogation of retinal activity, understanding the underlying mechanisms 15, 39,45 of such optoretinograms is key for its application as a biomarker to study basic visual processes and retinal health in disease and therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The agreement of the model with the experimental results, being consistent in peak deformation and timing across all stimulus strengths with a single set of model parameters (m, c, k, and l), indicates that contraction of the outer segment is indeed driven by the charge transfer across the membrane during ERP. A more detailed description of the model linking the underlying biophysical properties of the membrane to these phenomenological parameters is described elsewhere (33).…”
Section: Mechanism Of Cone Outer Segment Contractionmentioning
confidence: 99%